Evaluating the Role of the Taxpayer Compliance Committee in Risk-Based Taxpayer Supervision: A Case Study Using Dunn’s Policy Evaluation Framework - Mohammad Hadika Satya Hasan; Panggah Tri Wicaksono (Universitas Pendidikan Ganesha, 2026)
The growing volume of digital economic and cross-border transactions had made manual-based supervision increasingly ineffective. The Directorate General of Taxes (DJP) has responded by implementing Compliance Risk Management (CRM) and Business Intelligence since July 2021, including forming Compliance Committee. However, studies specifically examining the role of Compliance Committee in supporting CRM implementation at the tax office remains limited. To address this gap, this study aimed to evaluate the role of the Taxpayer Compliance Committee at the Jakarta Gambir Dua Tax Office in supporting tax supervision activities using qualitative research with a case study approach. Data were collected through document analysis and in-depth interviews with members of the Compliance Committee and Account Representatives. William Dunn’s (2018) policy evaluation criteria, consisting of effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness, were applied as the evaluation framework. The findings indicated that the Compliance Committee had been effective in encouraging follow-up actions on supervision results, cost-efficient but in need of strengthened time management, adequate in terms of the availability of information resources, equitable in its processes, technically responsive, and appropriate as an instrument of risk-based tax supervision policy. This evaluation contributes to the literature by providing evidence on how Taxpayer Compliance Committee could support the CRM implementation. Practically, it provides actionable insight for strengthening risk-based supervision at the Tax Office level.